Methodology of da'wah to the non-Muslim chinese in Malaysia: a preliminary observation - Abdullah @ Chuah Hock Leng, Osman (Universiti Sains Islam Malaysia (USIM), 2006)
Methodology of Da'wah especially to non-Muslims is very vital for the preachers to observe the proper norms in the Islamic perspective nowadays. In the context of preaching to non-Muslim Chinese in Malaysia, the preachers must understand their backgrounds arid their perceptions towards Islam before preaching. This article highlights the 'non-Muslim Chinese negative perceptions towards Islam and its ummah and suggest means and approaches of preaching with hikmah to bring Islam to the non-Muslim Chinese in Malaysia.